ANALISIS KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA SEMARANG (Students' Journal of Accounting and Banking, 2013)
The income from local own revenues is an important sources for routine expenditure and development expenditure in local government. The amount of local taxation and local retribution income are influenced by the kind of local taxation and local retribution which is being implemented and adjusted by the rule that is implemented, related with income of local taxation and local retribution. The research is analyzed contribution of local taxation and local retribution income to acceptance of local own revenues in Semarang in the period of budget years 2008-2011. The Contribution of local tax revenues and local retribution to the local own revenues of Semarang City in the period of budget years 2008 - 2010 is significant with an average contribution of local taxation by 52.73 percent per year. While the average contribution of local retribution amounting to 26.34 percent per years. To increase the ability of local governments to implement local autonomy, central government sets Statute 28 year 2009 about local taxation and local retribution. The results in 2011 in the local own revenues of Semarang city increased 59.01 percent from the previous year. Contribution Local Tax to the local own revenue also increased to reach 69.04 percent. Keywords: Local own revenues, local taxation, and local retribution